HUBUNGAN TIPE INDUSTRI DAN UKURAN PERUSAHAAN TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) - Aisyah Aisyah (AkMen JURNAL ILMIAH, 2017)
Independent variables (industry type, company size) simultaneously or together have influence on the dependent variable (Corporate Social Responsibility (CSR)) where in table F with α: 0.05 obtained F table value of 2.76 and F count of 3.126 or Fcount> Ftable. 4. Partially the variable that has significant influence is the size of the company, where the value of T table: 1.699 smaller than the value Thitung: 3.365. 5. The influence of independent variable, that is industry type, and company size, to variable Y, that is Corporate Social Responsibility (CSR) is equal to 27,1% while the rest equal to 72,9% is influence sourced from other variable not examined